2023
DOI: 10.1021/acs.inorgchem.3c00355
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Nickel Complexes as Effective and Versatile Catalysts for Copolymerization of Epoxides with Carbon Dioxide or Phthalic Anhydride: Catalysis and Kinetics

Abstract: This study reported three novel structurally wellcharacterized dihalide dinuclear nickel complexes containing benzotriazole-based 1,3-diamine-linked bisphenolate ligands, which were highperformance catalysts for ring-opening copolymerization (ROCOP) of cyclohexene oxide (CHO) and carbon dioxide (CO 2 ). The dinickel diiodo 3 was shown to catalyze CO 2 copolymerization of CHO with high activity (turnover frequency up to 2250 h −1 ), excellent selectivity (>99% polycarbonates, >99% carbonate repeated units), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…These results indicated that not only did the acetate moiety initiate the polymer chain growth, but also the chain transfer copolymerization took place because of the presence of protic species during the catalytic process. 33,47 For comparison of catalytic performances for nickel complex-mediated CO 2 /CHO copolymerization, structurally-related dicarboxylate dinickel complexes containing various N-heterocycle-based 1,2-diamine-bisphenolate ligands were chosen, as shown in Scheme S2 †. These selected binickel complexes ( A–C and 1 ) include ligand scaffolds that contain benzotriazole, pyrazolyl, benzothiazole or imidazole groups as the pendant heterocycle donor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that not only did the acetate moiety initiate the polymer chain growth, but also the chain transfer copolymerization took place because of the presence of protic species during the catalytic process. 33,47 For comparison of catalytic performances for nickel complex-mediated CO 2 /CHO copolymerization, structurally-related dicarboxylate dinickel complexes containing various N-heterocycle-based 1,2-diamine-bisphenolate ligands were chosen, as shown in Scheme S2 †. These selected binickel complexes ( A–C and 1 ) include ligand scaffolds that contain benzotriazole, pyrazolyl, benzothiazole or imidazole groups as the pendant heterocycle donor.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the development of the binickel-complex-catalyzed copolymerization of CO 2 with alicyclic epoxides by nitrogen-containing heterocycle-derived phenolate derivatives has been achieved by our group. 28–33 The ligand frameworks in these bimetallic Ni complexes are mainly attributed to N-heterocycle-based bis(iminophenolate) and bis(aminophenolate) derivatives, which can take part in O 2 N 4 -hexadentate chelation for the construction of dinuclear nickel complexes. Among these ligand scaffolds, several different N-involving heterocyclic moieties, such as benzotriazole, pyrazolyl and benzothiazole groups, were successfully bonded to diamine-bisphenolates, as exhibited by types A–C in Chart 1, and the corresponding dinickel complexes could be synthesized to evaluate their catalytic performances for the ROCOP of CHO with CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we found that different acid–base conditions resulted in the synthesis of diverse structures. All nickel and copper complexes were characterized through UV–vis spectra (Figure S1), elemental analysis, and single-crystal X-ray crystallography …”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] In addition, the resulting copolymers (bearing esters and carbonate functionalities) possess, in principle, cleavable bonds with the possibility of obtaining hydrolyzable polymeric materials. [7][8][9][10] Indeed, ROCOP is usually catalyzed by metal complexes with various ligand frameworks [11][12][13] able to activate the ring opening of the epoxides and the alternating insertion of the cyclic anhydride or CO 2 following the reaction pathways depicted in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%